Non-literary in the Light of Literary Translation - Newmark, Peter (2022)
The purpose of this article is to contrast non-literary with literary translation. An example from the opening pages of Kafka’s Amerika is used to illustrate how literary texts may be translated differently from non-literary ones. They differ essentially through intention (literary texts belong to the world of imagination whereas non-literary ones belong to the world of facts) and through the fact literary texts are about persons while non-literary ones are about objects. Nevertheless, both texts are concerned with the fundamental truths of translation: factual, aesthetic, allegorical truth, logical and linguistic truth.